'They will not control us': ingroup positivity and belief in intergroup conspiracies - Cichocka, A. (2016)
This research examined the role of different forms of positive regard for the ingroup in predicting beliefs in intergroup conspiracies. Collective narcissism reflects a belief in ingroup greatness contingent on others' recognition. We hypothesized that collective narcissism should be especially likely to foster outgroup conspiracy beliefs. Non-narcissistic ingroup positivity, on the other hand, should predict a weaker tendency to believe in conspiracy theories. In Study 1, the endorsement of conspiratorial explanations of outgroup actions was positively predicted by collective narcissism but negatively by non-narcissistic ingroup positivity. Study 2 showed that the opposite effects of collective narcissism and non-narcissistic ingroup positivity on conspiracy beliefs were mediated via differential perceptions of threat. Study 3 manipulated whether conspiracy theories implicated ingroup or outgroup members. Collective narcissism predicted belief in outgroup conspiracies but not in ingroup conspiracies, while non-narcissistic ingroup positivity predicted lower conspiracy beliefs, regardless of them being ascribed to the ingroup or the outgroup.